A Close Analysis of Buyers and Antitrust Markets - Warren G. Lavey (Washington University Law Quarterly, 1983)
This Article describes a procedure for ascertaining the proper universe of buyers in a market and using this identified group of buyers to define relevant product and geographic markets. The "affected-buyers" analysis recommended in this Article involves three steps. First, identify a group of buyers with a common demand. A firm attempting to increase its price to this group for some output satisfying this common demand may be likely to find that its sales to other buyers are affected as well. Second, designate the "common demand" group plus these other likely affected buyers as the proper universe of buyers for defining the relevant markets. Third, define the relevant product and geographic markets according to the close demand and supply substitutes for the properly designated universe of buyers. After describing and illustrating affected-buyers analysis, this Article examines two common approaches to defining antitrust markets and explains their flaws. One approach, the "firm-competitors" model, starts the analysis with the firm and attempts to identify its competitors. For example, if a firm has allegedly monopolized sales of a certain product, this approach defines the relevant market as sellers which could sell substitutes to some or all of the firm's buyers. A second approach, the "buyers-alternatives" model, posits particular buyers with similar demand and attempts to identify the firms competing to sell to them. Under this approach, if the claim is that a firm monopolizes sales of a certain product to particular buyers, the firms which could sell substitutes to these buyers comprise the relevant market. Finally, this Article evaluates the merger guidelines issued by the Department of Justice and the Federal Trade Commission in 1982 against the proposed affected-buyers model.
Keywords: Antitrust law; Economics; Market share; United States. Department of Justice. Antitrust Division; United States. Federal Trade Commission; United States